Ovarian sensitivity index is a better measure of ovarian responsiveness to gonadotrophin stimulation than the number of oocytes during in-vitro fertilization treatment - Li, Hang Wun Raymond; Lee, Vivian Chi Yan; Ho, Pak Chung; Ng, Ernest Hung Yu (Journal of assisted reproduction and genetics, 2014)
Purpose To validate the use of the ovarian sensitivity index (OSI) as a measure of ovarian response during in-vitro fertilization (IVF) treatment. Methods This is a retrospective study carried out in an assisted reproduction unit in a teaching hospital. We analysed data from 2,556 women undergoing the first IVF cycle between 2002 and 2009. OSI was calculated as the number of retrieved oocytes divided by total dose of FSH administered (per 1,000 IU). Its correlation to other parameters of ovarian response was compared to that of the oocyte number. Results The correlation coefficients of OSI with age, AFC, AMH, total dose of gonadotrophin, average daily dose of gonadotrophin and duration of stimulation were significantly higher than that of oocyte number with these respective parameters. OSI demonstrated a higher intraclass correlation coefficient (ICC) than the oocyte number when comparing the two parameters across the first and second stimulated IVF cycles. Conclusions OSI is a better measure of ovarian responsiveness to gonadotrophin stimulation than the oocyte number, and is particularly useful when different subjects are treated with different stimulation regimens which would have confounding effect on the oocyte number.